Critical directions in comics studies - Giddens, Thomas (University Press of Mississippi, 2020)
An examination of the cutting-edge critical engagement in the field of modern comics studies
Description based on publisher supplied metadata and other sources
Keywords: Comic; Electronic books; Aufsatzsammlung